Identifying and solving Islamic religious education challenges for special needs children - Pandia, Weny Safitri S.; lautzy, Omar; Drew, Anson (CV. BImbingan Belajar Assyfa, 2023)
To achieve strict compliance and devotion to Allah SWT, special needs children must get a thorough Islamic education. Islam also has Rukhsah, which accommodates labourers who struggle to fulfil their religious duties. This discipline of science studies Sharia law as it applies to people with special needs. Thus, ignoring religion is unjustified. However, teaching Islamic religious education to special needs children is difficult due to their inability to understand abstract concepts and the necessity for concrete explanations. Thus, Islamic Religious Education instructors must use strategies that help SLB students, including those with special needs, understand the curriculum. A literature review of relevant studies examines Islamic religious education learning for special needs children in many special schools. This investigation is intriguing and subjective. The literature review examines PAI instructors and students who work with special needs children. The study covers PAI learning examinations for special-needs youngsters. In contrast, the literature review cites coworkers, guardians, and teachers. Data is collected through observations, conferences, and writing. The information used for the investigation is. According to this investigation, the Madrasah Ibtidaiyah Learning Examination for special needs children in numerous special schools may still be educational and learning exercises. Guides and unusually paired students accompany students with special needs during growth. Teachers will help students with special needs learn even if they are not grouped. This essay will analyze the barriers to PAI learning for special needs children.